Bibliometric Analysis of Food and Post-Harvest Research in Enhancingthe Integrity of Halal Food Industry - Redika Ardi Kusuma; Devi Yuni Susanti; Sri Maryati; Jumeri Jumeri (Universitas Darussalam Gontor, 2023)
Halalness of products has been a global concern in recent years due to increasing awareness, especially in Muslim-populated countries. However, Indonesia, the country with the largest Muslim population in the world, is only ranked 5th in halal industry development. Therefore, producers and consumers are expected to have a deeper understanding of halal practices that can encourage the development of industries with halal-certified products. This paper aimed to systematically and quantitatively plot the output of scientific research on implementing food and postharvest technology to improve the integrity of the halal food industry. The research method was bibliometric analysis using VOSviewer as a mapping tool. This research has four stages: (i) collection of bibliometric data from the Scopus database, (ii) performance analysis using embedded Scopus analysis tool, (iii) data mapping using VOSviewer, and (iv) mapping data analysis. Out of 2,875, only 161 keywords from 455 articles met the analysis threshold. The results showed that the topic of meat received the most attention from 2008 to 2021, found in 84 articles with 878 total link strengths. Furthermore, one of the most cited research topics recently was related to modeling the theory of planned behavior with factors of Halal awareness, certification, food quality, promotion, and brand on the intention to purchase halal products by non-Muslim consumers, with203 citations from 2013 to 2021. In general, researchers can use this study to examine trends and directions of future research topics comprehensively